Introduction: Higher education reform in the 'periphery'. Issue 1 (1st March 2019) - Ivancheva, Mariya; Syndicus, Ivo
Abstract : In recent years, an increasing body of work has addressed the 'corporatisation' and 'commodification' of universities, as well as higher education sector reforms more broadly. This work refers mostly to the traditional core hubs of higher education, such as the Anglo-American research university. In the emerging anthropology of higher education policy, accounts of the implementation and negotiation of reforms in more 'peripheral' contexts often remain absent. This collection of articles addresses this absence by focusing on the interplay between narratives of global policy reform and the processes of their implementation and negotiation in different contexts in the academic 'periphery'. Bringing together work from a range of settings and through different lenses, the special issue provides insights into the common processes of reform that are underway and how decisions to implement certain reforms reaffirm rather than challenge peripheral positions in higher education.